2015
DOI: 10.9713/kcer.2015.53.4.440
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Operating Variables on the Solid Circulation Rate in a Three-phase Circulating Fluidized Bed

Abstract: − Effects of operating variables on the solid circulation rate were investigated in a three-phase circulating fluidized bed, of which inside diameter was 0.102m and height was 3.5m, respectively. Gas velocity, primary and secondary liquid velocities, particle size and height of solid particles piled up in the solid recycle device were chosen as operating variables. The solid circulation rate increased with increasing primary and secondary liquid velocities and height of solid particles piled up in the solid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(25 reference statements)
1
1
0
Order By: Relevance
“…The steady-state Gs is 0.66, 0.615, and 0.46 kg (m 2 s) −1 , respectively. As the d p increases, the ratio of U lc to U t gradually increases, but the corresponding stable G S decreases, which is consistent with the conclusion obtained by Kang et al 16,43 on macroscopic three-phase circulating fluidized beds. The delayed transition is attributed to the strengthened wall effect caused by an increase in d p , which has also been discovered in related studies on liquid− solid microcirculating fluidized beds.…”
Section: Effect Of Particlesupporting
confidence: 91%
“…The steady-state Gs is 0.66, 0.615, and 0.46 kg (m 2 s) −1 , respectively. As the d p increases, the ratio of U lc to U t gradually increases, but the corresponding stable G S decreases, which is consistent with the conclusion obtained by Kang et al 16,43 on macroscopic three-phase circulating fluidized beds. The delayed transition is attributed to the strengthened wall effect caused by an increase in d p , which has also been discovered in related studies on liquid− solid microcirculating fluidized beds.…”
Section: Effect Of Particlesupporting
confidence: 91%
“…Considering the effects of operating variables on ε S , it was found that the value ε S increased with increasing U G , d P or G S but decreased with increasing U L or μ L in TPCFBs as shown in Figures 3 and 4 (Cho et al, 2001a;Liu et al, 2003;Vatanakull et al, 2003;Razzak et al, 2007Razzak et al, , 2009). Regarding the G S in TPCFBs, Kim et al (2015) suggested Eq.…”
Section: Three-phase Circulating Uidized Beds (Tpcfbs)mentioning
confidence: 99%